ECONOMIC RECOVERY STRATEGY FOR THE COMMUNITY AND MSME PERFORMERS IN MEDAN CITY IN THE ADAPTATION ERA OF NEW HABITS - Yusrita, Yusrita (CV. Radja Publika, 2022)
This contemplate directs to ascertain : the contemplate of economical convalescence procedures from the consequence of Covid 19 during the conformableness amplitude to contemporary conventions look after the needs of as contemplate substantial and considerateness in formulating procedure manufacturing accompanying to the acceleration of the convalescence of MSMEs in the municipality of city which are pretentious by the consequence of the Covid 19 pandemic. classifications of collections in the contemplate these are influential collections and less important collections . The disposition of assembling collections is simple serendipitous sampling, videlicet the disposition euphemistic pre-owned to appropriate a exemplification from the inhabitant in much a course of action that each colleague of the inhabitant has the corresponding fighting chance to be appropriated as a sample. The collections psychoanalysis disposition euphemistic pre-owned is a qualitative psychoanalysis method, videlicet the psychoanalysis cognitive semantics that is supported on the continuance of a semantic communication between the variables continuance studied.